1982
DOI: 10.1037/0097-7403.8.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Serial discrimination reversal learning in the pigeon: Potentiation of "pattern" by a conditional cue.

Abstract: Six experiments were performed in which pigeons were trained daily on a conditional serial discrimination reversal problem. In the standard training procedure, on odd-numbered days a vertical line was superimposed on a successive wavelength discrimination task. On even-numbered days a horizontal line was superimposed on the reverse wavelength discrimination task. Experiments 1, 2, and 3 assessed the degree of control acquired by the compound conditional cues (lines plus "days") and by the component elements (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…On the day following the generalization test, the birds were retrained under Problem 1/Context 1 conditions, receiving the first of 20 sessions-in which the two problems, along with their paired contexts, were alternated on a daily basis. This procedure was called conditional serial discrimination reversal (CSDR) training by Thomas and McKelvie (1982) who used it to establish conditional control over a wavelength discrimination and its reversal by vertical and horizontal lines on the response key. On the day after the 20th session of CSDR training, the birds received a second wavelength generalization test in extinction administered under the same conditions as the first.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the day following the generalization test, the birds were retrained under Problem 1/Context 1 conditions, receiving the first of 20 sessions-in which the two problems, along with their paired contexts, were alternated on a daily basis. This procedure was called conditional serial discrimination reversal (CSDR) training by Thomas and McKelvie (1982) who used it to establish conditional control over a wavelength discrimination and its reversal by vertical and horizontal lines on the response key. On the day after the 20th session of CSDR training, the birds received a second wavelength generalization test in extinction administered under the same conditions as the first.…”
Section: Methodsmentioning
confidence: 99%
“…Several points should be made about this result. In the Thomas and McKelvie (1982) CSDR study conditional control was revealed in performance during training; however, the conditional cues were lines projected on the response key, and 40 sessions of CSDR training, rather than 20, were administered. Perhaps additional training would have revealed conditional control in training performance in the present experimental situation as well.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas and McKelvie (1982) obtained conditional discrimination learning with key color and line angle combinations, but they used extensive training (i.e., 40 sessions) and a daily reversal rather than a single reversal procedure. If a means were used to prevent the configuring of these cues, brief training and a single reversal procedure might also be effective.…”
mentioning
confidence: 99%
“…Boneau & Honig, 1964;Richards , 1979). Intermediate between these extremes is conditional serial discrimination reversal learning (CSDR ) as used by Thomas and McKelvie (1982). In their study, a wavelength discrimiRequests for reprintsshouldbe addressed to David R. Thomas, Department of Psychology, Campus Box 345, University of Colorado.…”
mentioning
confidence: 99%